UJI EFEKTIVITAS DAN STABILITAS HAIR TONIC EKSTRAK BAWANG MERAH (Allium cepa L.) SEBAGAI PERANGSANG PERTUMBUHAN RAMBUT - Kartika Sari; Laurensia, Vivi; Bachri, Nurjannah; Mukhsin, Achmad; Indrawati, Teti (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
External skin protection is one of the functions of hair, hair loss and even baldness are common problems. This condition is caused by two factors, namely genetics and the surrounding environment. Shallots (Allium cepa L.) are tubers that are used as a spice and medicine. The flavonoid and phenol content as antioxidants can rejuvenate and repair damaged hair cells, quercetin and kaempferol increase hair growth and prevent hair loss. This research aims to obtain a hair tonic preparation that has activity as a hair fertilizer and to obtain a hair tonic preparation that has good stability, is safe and efficacious. This research used experimental methods, effectiveness testing with Tanaka and accelerated stability testing. The effectiveness test results of healthy control, negative control, positive control, F2, F3 and F4 on the 21st day showed values respectively 12.8, 12.55, 17. .2, 16.5, 14.45 and 12.2 and stability test pH 5.73-6.82, density 0,990-1,031, brown color, liquid form, aromatic smell. The results showed that the preparation with F2 had the same results as the positive control and had a stable preparation in stability testing for 28 weeks.